Towards easy setup of robotic assembly tasks. (17th April 2020) - Sloth, Christoffer; Kramberger, Aljaž; Iturrate, Iñigo
ABSTRACT: There is a growing need for adaptive robotic assembly systems that are fast to setup and reprogram when new products are introduced. The World Robot Challenge at World Robot Summit 2018 was centered around the challenge of setting up a flexible robotic assembly system aiming at changeover times below 1 day. This paper presents a method for programming robotic assembly tasks that was initiated in connection with the World Robot Challenge that enables fast and easy setup of robotic insertion tasks. We propose to program assembly tasks by demonstration, but instead of using the taught behavior directly, the demonstration is merged with assembly primitives to increase robustness. In contrast to other programming by demonstration approaches, we perform not only one demonstration but a sequence of four sub-demonstrations that are used to extract the desired robot trajectory in addition to parameters for the assembly primitive. The proposed assembly strategy is compared to a standard dynamic movement primitive and experiments show that the proposed assembly strategy increases the robustness towards pose uncertainties and significantly reduces the applied forces during the execution of the assembly task. GRAPHICAL ABSTRACT: